Dormancy break in seeds of "quina" (Strychnos pseudoquina A. St.-Hil.) Superação da dormência de sementes de quina (Strychnos pseudoquina A. St.-Hil.) - J.M. Vasconcelos; M.A. Rodrigues; S.C. Vasconcelos Filho; J.F. Sales; F.G. Silva; J.G. Santana (Universidade Estadual Paulista, 2011)
"Quina" (Strychnos pseudoquina A. St. Hil) is a medicinal plant species from the Brazilian Cerrado. As its seeds show dormancy, they were subjected to the treatments pre-cooling at 5ºC during 7 days, pre-heating at 40ºC during 7 days, pre-soaking in sulfuric acid PA during 5 and 15 min, pre-soaking in boiling water during 5 and 15 min, pre-soaking in 100 and 200 ppm gibberellic acid during 48 h, pre-soaking in distilled water during 24 and 48 h, and mechanical scarification to break dormancy. Counts were daily conducted from the 2nd day after the experiment implementation until the germination stabilization at the 65th day. The germination speed index (GSI) and the germination percentage were evaluated. Germination rates above 96% were reached in seeds pre-soaked in water during 48 h and substrate moistened with water or KNO3. A quina (Strychnos pseudoquina A. St.-Hil) é espécie medicinal do Cerrado Brasileiro. As sementes apresentam dormência e, por isso, foram submetidas aos tratamentos pré-resfriamento a 5ºC durante 7 dias, pré-aquecimento a 40ºC durante 7 dias, pré-embebição em ácido sulfúrico P.A. durante 5 e 15 minutos, pré-embebição em água fervente durante 5 e 15 minutos, pré-embebição em ácido giberélico a 100 e 200 ppm, durante 48 horas, pré-embebição em água destilada durante 24 e 48 horas e escarificação mecânica, visando à superação da dormência. Foram realizadas contagens diárias entre o 2º dia após a implantação do experimento até a estabilização da germinação, que ocorreu no 65º dia. Foram avaliados o índice de velocidade de germinação (IVG) e a porcentagem de germinação. Taxas de germinação acima de 96% foram atingidas em sementes pré-embebidas em água durante 48 horas e substrato umedecido com água ou KNO3.